Parallel Independent Losses of G-Type Lysozyme Genes in Hairless Aquatic Mammals. (27th August 2021) - Zhang, Xiaoqing; Chi, Hai; Li, Gang; Irwin, David M; Zhang, Shuyi; Rossiter, Stephen J; Liu, Yang
Abstract: Lysozyme enzymes provide classic examples of molecular adaptation and parallel evolution, however, nearly all insights to date come from chicken-type (c-type) lysozymes. Goose-type (g-type) lysozymes occur in diverse vertebrates, with multiple independent duplications reported. Most mammals possess two g-type lysozyme genes ( Lyg1 and Lyg2 ), the result of an early duplication, although some lineages are known to have subsequently lost one copy. Here we examine g-type lysozyme evolution across >250 mammals and reveal widespread losses of either Lyg1 or Lyg2 in several divergent taxa across the mammal tree of life. At the same time, we report strong evidence of extensive losses of both gene copies in cetaceans and sirenians, with an additional putative case of parallel loss in the tarsier. To validate these findings, we inspected published short-read data and confirmed the presence of loss of function mutations. Despite these losses, comparisons of selection pressures between intact g- and c-type lysozyme genes showed stronger purifying selection in the former, indicative of conserved function. Although the reasons for the evolutionary loss of g-type lysozymes in fully aquatic mammals are not known, we suggest that this is likely to at least partially relate to their hairlessness. Indeed, although Lyg1 does not show tissue-specific expression, recent studies have linked Lyg2 expression to anagen hair follicle development and hair loss. Such a role for g-type lysozyme would explain why the Lyg2 gene became obsolete when these taxa lost their body hair.